Melychiopharis: an atypical orb-weaving spider from South America (Araneae: Araneidae) - Santos, Adalberto J.; Brescovit, Antonio D.; Levi, Herbert W. (Zootaxa, 2005)
The monotypic genus Melychiopharis Simon is transferred from Theridiidae to Araneidae, based mainly on characteristics of the male palp. Melychiopharis cynips Simon 1895 is redescribed and illustrated, including the first illustrations of a male specimen.